Marching to the mountaintop how poverty, labor fights, and civil rights set the stage for Martin Luther King, Jr.'s final hours - Bausum, Ann. (Washington, D.C. : National Geographic, 2012)
One minute she could see a sanitation worker struggling to climb out of the refuse barrel of a city garbage truck. The next minute mechanical forces pulled him back into the cavernous opening. It looked to her as though the man's raincoat had snagged on the vehicle, foiling his escape attempt. "His body went in first and his legs were hanging out," said the eyewitness, who had been sitting at her kitchen table in Memphis, Tennessee, when the truck paused in front of her home. Next, she watched the man's legs vanish as the motion of the truck's compacting unit swept the worker toward his death. "The big thing just swallowed him," she reported.
Foreword -- Introduction -- Death in Memphis -- Strike! -- Impasse -- A war on poverty -- Marching in Memphis -- Last days -- Death in Memphis, reprise -- Overcome -- Afterword -- King's campaigns -- Cast of characters -- Timeline -- Research notes and acknowledgments -- Resource guide.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes bibliographical references and index.
Description based on print version record.
Keywords: King, Martin Luther, -- Jr., -- 1929-1968 -- Juvenile literature; King, Martin Luther, -- Jr., -- 1929-1968 -- Assassination -- Juvenile literature; Sanitation Workers Strike, Memphis, Tenn., 1968 -- Juvenile literature; Labor movement -- Tennessee -- Memphis -- History -- 20th century -- Juvenile literature; African Americans -- Tennessee -- Memphis -- Social conditions -- 20th century -- Juvenile literature; Memphis (Tenn.) -- Race relations -- History -- 20th century -- Juvenile literature; Electronic books- OSLIS; Electronic books